Effects of dietary Solanum nigrum L. supplementation on growth performance, antioxidant capacity, ileal transcriptomic profile, and cecal microbiome in Wuhua yellow-feathered chickens - Zhang, Mengling; Li, Yunlei; Cai, Mengkai; Li, Meidi; Huang, Rihao; Xu, Weilin; Liu, Xiaoyan; Xiong, Yanqing; Jia, Congjun (Frontiers in Animal Science, 2025)
Although studies have investigated Solanum nigrum L. (SNL) in mice, its effects on broilers remain unclear. This study examined how dietary SNL influences growth performance, antioxidant capacity, ileal transcriptome, and gut microbiota in broilers. A total of 200 one-day-old healthy Wuhua yellow-feathered chickens were randomly divided into four groups of five replicates (10 birds each). The groups received: a basal diet (CON), a basal diet with 500 mg/kg amoxicillin (AMO), a basal diet with 1000 mg/kg SNL grass meal (0.1% SNL), and a basal diet with 2000 mg/kg SNL grass meal (0.2% SNL). The experiment lasted 35 days. SNL supplementation modestly improved feed efficiency and jejunal villus height (p = 0.019). It also altered cecal microbiota by increasing Bacteroidetes, Bacteroides, and Faecalibacterium, while decreasing Firmicutes and Oscillibacter. Ileal transcriptomics identified multiple differentially expressed genes (DEGs) across comparisons, which were enriched in intestinal immune network pathways for IgA production. Correlation analysis linked cecal microbiota changes to ileal gene expression. In conclusion, SNL exhibits the potential as an alternative to antibiotics in chickens, and this study provides empirical support for its broader adoption in poultry industry.